2020
DOI: 10.33899/ijvs.2019.125557.1076
|View full text |Cite
|
Sign up to set email alerts
|

Some anti-diabetic properties of Prosopis farcta extracts in alloxan induced diabetic in adult rats

Abstract: Prosopis farcta is belonged to Mimosaceae family, commonly known as mesquite. It was chosen to investigate their effect on α-glucosidase inhibitory activity (in-vitro), serum glucose and liver functions. Roots, fruits, and leaves of P. farcta, were extracted by n-hexane, ethyl acetate, and methanol. α-glucosidase inhibition was analyzed by using ELISA technique then half maximal inhibitory concentration IC50 was found. The blood glucose levels were determined with a glucose analyzer model. The serum alkaline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…These modulatory effects of RS were agreed with Takemura et al (20). Resveratrol can be protecting renal tubular epithelial cells through down-regulation of TLR4, NF-κB pathway, and reduced cell apoptosis in renal ischemia-perfusion injury model (21). Furthermore, resveratrol effectively restored SIRT1/3 activity, reduced acetylated SOD2 levels, ameliorated mitochondrial dysfunction of renal tubular epithelial cells, and improved kidney function by its antiinflammatory activity and anti-inflammatory activity, improving the metabolic memory of hyperglycemia (22).…”
Section: Discussionsupporting
confidence: 86%
“…These modulatory effects of RS were agreed with Takemura et al (20). Resveratrol can be protecting renal tubular epithelial cells through down-regulation of TLR4, NF-κB pathway, and reduced cell apoptosis in renal ischemia-perfusion injury model (21). Furthermore, resveratrol effectively restored SIRT1/3 activity, reduced acetylated SOD2 levels, ameliorated mitochondrial dysfunction of renal tubular epithelial cells, and improved kidney function by its antiinflammatory activity and anti-inflammatory activity, improving the metabolic memory of hyperglycemia (22).…”
Section: Discussionsupporting
confidence: 86%
“…The alloxan dose was optimized through earlier trials (data not shown). Subsequently experimental rats were given a 20% dextrose solution after four hours of alloxan injection to avoid alloxan induced hypoglycemia in rats due to excessive discharge of insulin from necrotic pancreas (Mohammed, Kakey et al 2020). All experimental rats were maintained on 5% glucose in drinking water (Kumar, Nandakumar et al 2011) for next 24 hours.…”
Section: Induction Of Diabetes Mellitusmentioning
confidence: 99%